Chinese fans of Japanese and Korean pop culture : nationalistic narratives and international fandom / Lu Chen. - Chen, Lu (Senior research assistant) (Routledge contemporary China ;, 2019)
How can Japanese popular culture gain numerous fans in China, despite pervasive anti-Japanese sentiment? How is it that there's such a strong anti-Korean sentiment in Chinese online fan communities when the official Sino-Korean relationship is quite stable before 2016? Avid fans in China are raising hundreds of thousands of dollars in funding to make gifts to their idols in foreign countries. Tabloid reports on Japanese and Korean celebrities have been known to trigger nationalist protests in China. So, what is the relationship between Chinese fandom of Japanese and Korean popular culture and nationalist sentiment among Chinese youth? Chen discusses how Chinese fans of Japanese and Korean popular culture have formed their own nationalistic discourse since the 1990s.